2009
DOI: 10.1017/s0021932008002885
|View full text |Cite
|
Sign up to set email alerts
|

Health-Seeking Behaviour for Childhood Malaria: Household Dynamics in Rural Senegal

Abstract: Research on health care behaviour in sub-Saharan Africa usually considers the mother as the reference in the household when a child is sick. The study of health care management within the family is a key issue for understanding therapeutic rationales. This study was conducted in the region of Fatick in Senegal among 902 children with malaria-related fever. The data were taken from a retrospective quantitative survey conducted in all compounds of the DSS (Demographic Surveillance Site) of Niakhar. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 16 publications
4
45
1
Order By: Relevance
“…However, passive surveillance may miss clinical episodes that are treated or resolve spontaneously without presentation to health care facilities[14], [15], [16]. Cohorts under active surveillance often record higher rates of malaria episodes than those under passive surveillance [17], [18] which may be interpreted either as the inclusion of false-positives by the former, or an under-estimation of the true malaria burden by the latter [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, passive surveillance may miss clinical episodes that are treated or resolve spontaneously without presentation to health care facilities[14], [15], [16]. Cohorts under active surveillance often record higher rates of malaria episodes than those under passive surveillance [17], [18] which may be interpreted either as the inclusion of false-positives by the former, or an under-estimation of the true malaria burden by the latter [19], [20], [21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, health education programmes in Malawi rarely seek to involve grandmothers [31]. Involving the wider community, including men and grandmothers in community-based education programmes in Malawi and elsewhere would ensure that all those involved in the treatment-seeking process are included [29, 31, 33, 34]. The role of older women should also be harnessed in behaviour change strategies [35]; involving grandmothers in health education programmes has been seen to lead to improvements in the education messages they give to mothers, and mothers’ health seeking behaviour [36].…”
Section: Discussionmentioning
confidence: 99%
“…Studies of individual care-seeking in many LMICs suggests a complicated process according to a number of factors, including symptom [4, 33, 36], consultation with household members [37–39], relying on prior experiences [40], perceived severity of illness [41], quality of care, provider reputation [42, 43], cost [7, 38], location [44], and use of multiple, concurrent treatments [4, 45, 46]. Our study of care-seeking showed that PPMV customer behavior also varied by many of these factors.…”
Section: Discussionmentioning
confidence: 99%